Influence of Anodic Aluminum Oxide Nanostructures on Resistive Humidity Sensing - Chin-An Ku; Chia-Wei Hung; Chen-Kuei Chung (Nanomanufacturing, 2024)
Humidity nanosensors play a vital role in modern technology industries, including weather forecasts, industrial manufacturing, agriculture, food and chemistry storage. In recent years, research on humidity sensors has focused on different materials such as ceramics, polymers, carbon-based materials, semiconductors, MXenes or triboelectric nanogenerators, each with their own advantages and disadvantages. Among them, anodic aluminum oxide (AAO) is a well-known ceramic humidity sensor material with a long history of research and development. AAO humidity sensors offer advantages such as simple manufacturing processes, controllable nanostructures, high thermal stability and biocompatibility. However, traditional AAO fabrication still has disadvantages like high costs and longer process times. Hence, finding a low-cost and efficient method to fabricate AAO for controlling different nanostructures to meet the requirements is consistently a major research topic. From our previous studies, we have studied the relationship between the AAO capacitive humidity sensor and its nanostructures. In this paper, we explore the effect of an AAO nanoporous structure controlled by an anodization voltage of 20–40 V on the resistive-type humidity sensor performance instead of a capacitive one. We efficiently apply one-step hybrid pulse anodization at 25 °C to significantly reduce the processing time compared to the traditional two-step process under 0–10 °C. The AAO nanostructures and their impact on sensor measurements of humidity at 20–80 RH% will be discussed in detail. An electrical resistive sensing mechanism is established for further performance improvement by controlling anodization voltage.